Encyklopedia doby średniopolskiej jako gatunek w formie kolekcji - Szczaus, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The aim of the article is a genological analysis of the oldest Polish-language encyclopedia, i.e. Informacyja matematyczna [Mathematical information] by Wojciech Bystrzonowski (first edition 1743). It is a continuous text divided into chapters devoted to various fields of knowledge included in the groups of topics that deal with theoretical and practical problems. This conception of text influenced its genre diversity: theoretical parts were overpowered by genres serving an informative function (e. g. description, list, index), but sometimes also a persuasive function (e. g. a treaty, a matter), while the practical parts included genres fulfilling a predominantly directive function (e. g. military regulations, instructions). The genres combining informative and ludic functions were also marginally present (e. g. Latin-language mnemotechnical poems woven into the text). Such extreme internal diversity of genres had several reasons: a) high diversity of topics, b) reference to silva rerum literary formula developed in the Baroque period, c) reference to and benefit from dozens of different studies conducted by Polish and Latin-language authors. Based on the example of selected parts of the text (e. g. descriptions), it was proved that we can observe in Bystrzonowski’s compendium a development process of a new genre, i.e. an encyclopedic entry.